The Effect of Using the Crew Inspector and Bassnet Applications on the Documentation System at PT Aweidhia Crew Management - Marihot Simanjuntak; Bambang Sumali; Shahnaz Rhein Ariata (Meteor STIP Marunda, 2023)
This study examines how the Crew Inspector and Bassnet applications affect the documentation system at PT. Aweidhia Crew Management. The research uses a quantitative approach with a census sampling method, surveying all 30 employees at the company. Data were collected through questionnaires using Likert scales and analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM) in SmartPLS 4.0. Both descriptive and inferential statistics were applied to assess the measurement and structural models. The results show that both applications have a significant positive effect on the documentation system, with the Bassnet application showing a stronger influence than Crew Inspector. The structural model explains 98.1% of the variance in documentation system performance, indicating that these two applications account for nearly all variation in documentation quality at the company.